NOTES ON THE ALL-RUSSIAN SEMINAR «FORENSIC EXAMINATION OF MANUFACTURED (NON-FOOD) PRODUCTS FOR EVALUATION AND OTHER PURPOSES», PYATIGORSK, SEPTEMBER 21–27, 2014 - A. Selivanov (Теория и практика судебной экспертизы)
.